Pierre-François Mourier, Cicéron. L’avocat et la République, París, Editions Michalons, 1996, 124 pp. (Minerva, 2019)
Review: Pierre-François Mourier, Cicéron. L’avocat et la République, París, Editions Michalons, 1996, 124 pp.